If it's not what You are looking for type in the equation solver your own equation and let us solve it.
10x+3=3(2x+1)-x+8
We simplify the equation to the form, which is simple to understand
10x+3=3(2x+1)-x+8
Reorder the terms in parentheses
10x+3=+(+6x+3)-x+8
Remove unnecessary parentheses
+10x+3=+6x+3-x+8
We move all terms containing x to the left and all other terms to the right.
+10x-6x+1x=+3+8-3
We simplify left and right side of the equation.
+5x=+8
We divide both sides of the equation by 5 to get x.
x=1.6
| -x+3+9x=-2+3x+10 | | -11c=89 | | 5=-3(x+2)-4 | | 6x+3+x=2+2x+21 | | 7x(4+4x)= | | 5x-4=2x+29 | | 5y=9 | | 0=9-5y | | 5x=-6 | | 10x=x+100 | | 6x+5=-2#-9 | | 4x^2-36x=-80 | | 6x+4x=65-3x | | 2+16/2+6=4 | | 3p^2-7p-6=0 | | x^3+2x^2+x-2=0 | | 3x^2-8x*3=0 | | 14m+2-27=m+3 | | -7t=-70 | | x^2-x-38=0 | | 12q=-24 | | -b=80 | | (8x+3)-x=8x+16 | | 4p=-4 | | -(5y+4)-(-4y-5)=-6 | | -13g=-52 | | -4n=-60 | | -5c=0 | | a^3x^2-2ax-1=0 | | 7k=-28 | | 15t^2+2t-1=0 | | 5x+2(1-x)=2(2x) |